ASSESSMENT OF THE EFFICIENCY OF SYSTEM FUNCTIONING RESTORATION OF ARMORED TANK EQUIPMENT NATIONAL GUARD OF UKRAINE - Pavlov, Yaroslav (Honor and Law, 2023)
The article reveals the sequence of determining the efficiency indicators of the system of restoring armored vehicles for the needs of units and parts of the National Guard of Ukraine. The article defines that in order to successfully solve service and combat tasks, it is necessary to make maximum use of the capabilities of the armored vehicle recovery system and to evaluate the effectiveness of its recovery. Special indicators are used to assess the state of the repair system for the restoration of armored vehicles, which are a numerical representation of measured values or their ratios. The existing methods of forecasting and quantitative assessment of the effectiveness of systems for the restoration of armored vehicles of units and units of the National Guard of Ukraine, disclosed in the materials of the article, require further improvement due to the development of a new scientific and methodological apparatus. The article examines the methodology for evaluating the effectiveness of the system of restoring armored vehicles of units and units of the National Guard of Ukraine in terms of the probability of meeting maintenance and repair needs and the length of time that damaged equipment remains in a malfunctioning state. It is proposed to use the generalized coefficient of the recovery system as an indicator of the effectiveness of the recovery system of armored vehicles. The methodology for assessing the effectiveness of the system for the restoration of armored vehicles should, on the one hand, ensure the necessary production capacity in wartime in a limited time with minimal additional costs, on the other hand, so that the costs of its maintenance in peacetime are minimal, but sufficient for current repair needs in the day-to-day activities of parts and subdivisions of National Guard of Ukraine. The disadvantage of the given methodology in relation to the comprehensive assessment of the effectiveness of the system of restoring armored vehicles is the lack of indicators of components of technical intelligence and evacuation of damaged samples of military equipment. This requires additional research into the factors that affect the quality of the functioning of the system for restoring damaged samples of self-armored vehicles of the National Guard of Ukraine units in combat conditions.